Tuhan Juga Mengasihi Kain: Menafsir Ulang Kejadian 4:13-16 dengan Lensa Psikoteologi Pengampunan Fraser Watts - Roy Charly Sipahutar; Lamria Sinaga; Agustinus Setiawidi (Program Pascasarjana UKIM, 2022)
In general, the remedies given to victims tend to neglect the psychological treatment of perpetrators. This study aims to make room for this handling, Genesis 4:13-16, which presents a dialogue between God and Cain, will be reinterpreted from the perspective of the Psycho-theology of Forgiveness according to Fraser Watts. In addition to avoiding the saturation of interpretation of this passage which is usually considered as the etiology of the dispute between the Israelites and the Kenites or the origin of family disputes, this perspective of forgiveness can also serve as a lens for constructing the wisest attitude when a person experiences human anger toward others. The result of the interpretation concludes that God is trying to restore Cain by giving forgiveness so that he can get out of his shame and can continue his life.